Ultrasound probe with progressive element sizing - Abend, Kenneth (2002)
A prior application discloses a novel probe geometry that offers a wide field of view in an ultrasonic imaging device. That geometry is referred to as a "thinned array" of transducer elements. The application discloses an improved probe geometry permitting high-resolution imaging of a large volume of the subject's body. In this improved geometry, the array elements are non-uniform in size and spacing. The probe is intended for use, for example, in a method of determining parameters of blood flow, such as vector velocity, blood flow volume, and Doppler spectral distribution, using sonic energy (ultrasound) and a novel thinned array. Also in a method of tracking blood flow and generating a three dimensional image of blood vessel of interest that has much greater resolution than images produced using heretofore known ultrasound devices and methods.